Positive plate and preparation method thereof
By setting up a two-layer structure with different material characteristics in the lithium-ion battery positive electrode sheet, the problem that ternary materials and lithium iron phosphate materials in the prior art cannot fully exert their characteristics, and higher battery performance and better safety are achieved.
Patent Information
- Application Number
- CN202411951805.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The use of ternary materials and lithium iron phosphate materials in existing lithium-ion batteries is only a simple combination, and the characteristics of the two materials cannot be fully utilized, resulting in the battery being unable to meet the needs in terms of energy density, cycling performance and power performance.
A positive electrode sheet structure is adopted, which includes a first positive electrode material layer with lithium iron phosphate and a second positive electrode material layer with ternary material. The porosity of the first positive electrode material layer is smaller than the porosity of the second positive electrode material layer to achieve peak diffusion of lithium ions and higher battery performance.
Through this structural design, the battery's charging rate lithium-ion window is improved, the power and safety performance are improved, and the circulation performance is significantly improved.
Smart Images

Figure CN119786516A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode sheet and a preparation method thereof. Background Art
[0002] At a time when smartphones and electric cars are popular, battery capacity and charge and discharge performance are critical parameters that can directly determine battery life and battery charging efficiency. At present, the batteries used in commercial applications are mainly lithium-ion batteries, and the type of active material in the positive electrode of lithium-ion batteries has a significant impact on the performance of the battery.
[0003] In the prior art, ternary materials and lithium iron phosphate materials are commonly used in lithium-ion batteries. Ternary materials have high gram capacity but face defects such as poor cycle performance and poor safety performance. Although lithium iron phosphate materials have low capacity and voltage platforms and poor conductivity, their cycle performance and safety performance are very good and are often used in energy storage fields and fields with high safety requirements. However, the simultaneous use of ternary materials and lithium iron phosphate materials in the prior art is only a simple combination, and the characteristics of the two different materials are not fully utilized at the same time, which cannot meet the current people's requirements for battery energy density, cycle performance and power performance.
[0004] Based on this, there is an urgent need to invent a positive electrode sheet and a preparation method thereof to solve the aforementioned technical problems. Summary of the invention
[0005] One of the purposes of the present invention is to provide a positive electrode sheet in view of the deficiencies of the prior art, which realizes the combined use of ternary materials and lithium iron phosphate materials, so that the charging rate lithium precipitation window of the battery with better power performance is improved, and has better safety performance.
[0006] In order to solve the above technical problems, this application adopts the following technical solutions:
[0007] Provided is a positive electrode sheet, comprising a current collector and a first positive electrode material layer coated on a surface of the current collector, and a second positive electrode material layer coated on a surface of the first positive electrode material layer away from the current collector, wherein the first positive electrode material layer comprises lithium iron phosphate, and the second positive electrode material layer comprises a ternary material, wherein the porosity of the first positive electrode material layer is less than that of the second positive electrode material layer.
[0008] In some embodiments, the porosity of the first positive electrode material layer ranges from 10% to 20%.
[0009] In some embodiments, the porosity of the second positive electrode material layer ranges from 30% to 40%.
[0010] In some embodiments, the thickness of the first positive electrode material layer is 70 um to 100 um, and the thickness of the second positive electrode material layer is 10 um to 30 um.
[0011] In some embodiments, the ratio of the ternary material to the lithium iron phosphate is between (1-3): (7-9).
[0012] In some embodiments, the ternary material includes at least one of NCM, NCA, and NCMA.
[0013] The beneficial effects of the present invention are as follows: the present application arranges a second positive electrode material layer having a ternary material on the outermost side of the positive electrode sheet, and arranges a first positive electrode material layer having lithium iron phosphate on the inner side. Since the ternary material has a layered structure, lithium ions have a two-dimensional diffusion channel, and the lithium ion diffusion efficiency is high, while lithium iron phosphate has a three-dimensional spatial network olivine structure, has a one-dimensional lithium ion diffusion channel, and has a low lithium ion diffusion efficiency. When the battery is charged at a high rate, lithium ions first diffuse from the ternary material to the negative electrode, and then diffuse from the lithium iron phosphate to the negative electrode, thereby achieving staggered diffusion of lithium ions to the negative electrode, reducing the sudden change of lithium ion concentration at the negative electrode, and reducing lithium precipitation at the negative electrode. In addition, the pores of the second positive electrode material layer are larger than those of the first positive electrode material layer, The pores of the second positive electrode material layer are set to be larger because the deformation of the ternary material during the deintercalation of lithium ions is larger. Providing a higher porosity can provide more expansion space for the ternary material, thereby improving the cycle performance of the second positive electrode material layer. Setting the porosity of the first positive electrode material layer to be smaller can increase the energy density of the first positive electrode material layer, and the diffusion rate of lithium ions can be controlled by setting the porosity size. Moreover, since the ternary material has good low-temperature performance, and the lithium iron phosphate material has good high-temperature performance, the battery can have better high-temperature performance and low-temperature performance by controlling the coordinated use of the ternary material and lithium iron phosphate. The battery prepared with the positive electrode sheet of the present application has better power performance, a higher charging rate lithium precipitation window, is not easy to undergo lithium precipitation, and has good cycle performance.
[0014] The second object of the present invention is to provide a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0015] Step 1: preparing a first positive electrode material layer slurry and a second positive electrode material layer slurry;
[0016] Step 2: selecting the thickness of the upper gasket and the lower gasket according to the solid content of the first positive electrode material layer slurry and the second positive electrode material layer slurry;
[0017] Step 3: Assembling the upper gasket and the lower gasket at the upper and lower cavity positions of the double-layer die head respectively;
[0018] Step 4: putting the first positive electrode material layer slurry and the second positive electrode material layer slurry into a buffer tank and assembling them with the double-layer die head;
[0019] Step 5: simultaneously coating the first positive electrode material layer slurry and the second positive electrode material layer slurry by double-layer die extrusion coating.
[0020] In some embodiments, the second positive electrode material layer slurry includes NCM, PVDF binder, methyl pyrrolidone NMP, conductive carbon SP, carbon nanotubes CNT, and the first positive electrode material layer slurry includes lithium iron phosphate main material LFP lithium iron phosphate, PVDF binder, methyl pyrrolidone NMP, conductive carbon SP, carbon nanotubes CNT.
[0021] In some embodiments, the solid content of the second positive electrode material layer slurry is 37% to 45%, and the solid content of the first positive electrode material layer slurry is 37% to 49%.
[0022] In some embodiments, the thickness of the upper gasket ranges from 0.6 to 0.8 mm, and the thickness of the lower gasket ranges from 0.8 to 1.0 mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet in the present invention;
[0025] Figure 2 This is one of the schematic diagrams of double-layer coating in the present invention;
[0026] Figure 3 This is the second schematic diagram of double-layer coating in the present invention.
[0027] Among them: 1 - current collector; 2 - first positive electrode material layer; 3 - second positive electrode material layer. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of the present application. The terms used herein in the specification of the present application are only for describing the embodiments in some embodiments and are not intended to limit the present application.
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings, but this is not intended to limit the present invention.
[0030] The applicant has found that the charging rate lithium precipitation window of the battery prepared by the positive electrode sheet of the existing ternary material as the active material and the positive electrode sheet of the lithium iron phosphate material as the active material is small, and it is easier to precipitate lithium at the negative electrode. This is because the positive electrode sheet of the ternary material is the active material, the lithium desorption speed of the ternary material is faster, and the ternary material has a two-dimensional diffusion channel. The lithium ion diffusion efficiency is high, and the lithium ion embedding space is large and the density is high. Lithium ions are easy to move, the movement path of lithium ions is short, and the migration rate of lithium ions to the negative electrode is high. When the battery is charged at a high rate, the negative electrode cannot embed these lithium ions in time. , which will cause lithium ions to accumulate on the surface of the negative electrode, thereby increasing the risk of lithium deposition at the negative electrode. For the positive electrode sheet with lithium iron phosphate as the active material, since lithium iron phosphate has a three-dimensional spatial network olivine structure, it has a one-dimensional lithium ion diffusion channel, low lithium ion diffusion efficiency, and low lithium ion conductivity. Therefore, the positive electrode sheet with lithium iron phosphate as the active material requires a higher voltage platform when charging at a high rate. When the voltage at the negative electrode is too high, the lithium ions on the surface of the negative electrode can no longer continue to be embedded in the lattice in a normal way, but are directly reduced to metallic lithium, causing the battery to deposit lithium when charged at a high rate.
[0031] To this end, the applicant uses both ternary materials and lithium iron phosphate materials in the positive electrode sheet according to their characteristics to achieve complementary advantages.
[0032] Example 1
[0033] like Figure 1 As shown, in this embodiment, a positive electrode sheet is provided, including a current collector 1 and a first positive electrode material layer 2 coated on the surface of the current collector 1, and a second positive electrode material layer 3 coated on the surface of the first positive electrode material layer 2 away from the current collector 1, the first positive electrode material layer 2 includes lithium iron phosphate, the second positive electrode material layer 3 includes a ternary material, wherein the porosity of the first positive electrode material layer 2 is less than the porosity of the second positive electrode material layer 3.
[0034] The first positive electrode material layer 2 with lithium iron phosphate is arranged closer to the current collector 1, and the second positive electrode material layer 3 with the ternary material is arranged on the outside. During charging, the lithium ions in the ternary material diffuse first, and the lithium ions in the lithium iron phosphate diffuse later, so that the lithium ions in the first positive electrode material layer 2 and the second positive electrode material layer 3 diffuse in an orderly manner, and the peaks of the migration rates of the lithium ions in the ternary material and the lithium iron phosphate material to the negative electrode are staggered, and the porosity of the first positive electrode material layer 2 is set to be smaller than the porosity of the second positive electrode material layer 3, so that the electrolyte has better infiltration into the second positive electrode material layer 3, and the rate at which the lithium ions in the second positive electrode material layer 3 diffuse to the negative electrode is faster. The maximum diffusion rate to the negative electrode is high, and the time to reach the highest diffusion rate to the negative electrode is short. The first positive electrode material layer 2 has a small pore, a small lithium ion transmission channel, and a longer lithium ion transmission distance, so it takes a longer time to achieve the highest migration rate to the negative electrode. By setting different porosities, the peak times of the maximum migration rates of lithium ions in the ternary material and the lithium iron phosphate material to the negative electrode are separated, reducing the overlap of lithium ion diffusion rates. In this application, by using the ternary lithium material and the lithium iron phosphate material together in the positive electrode sheet, the voltage required for high-rate charging of the battery will not be too high to cause lithium deposition at the negative electrode, and the migration speed of lithium ions will not be too fast to cause lithium ions to accumulate on the surface of the negative electrode to cause lithium deposition at the negative electrode.
[0035] Preferably, the porosity of the first positive electrode material layer 2 is in the range of 10% to 20%, and the porosity of the second positive electrode material layer 3 is in the range of 30% to 40%. When the porosity is within the above range, the distance of the transmission path of lithium ions in the first positive electrode material layer 2 is appropriate, the diffusion rate of lithium ions is appropriate, and the ternary material of the second positive electrode material layer 3 has appropriate expansion space when deintercalating and extracting lithium ions, which can improve the cycle performance of the second positive electrode material layer 3.
[0036] Preferably, the thickness of the first positive electrode material layer 2 is 70um to 100um, and the thickness of the second positive electrode material layer 3 is 10um to 30um. The transmission distance of lithium ions can be controlled by controlling the thickness of the material layer. When the thickness is set within the above range, the transmission distance of lithium ions in lithium iron phosphate and the ternary material is appropriate, which is beneficial to control the diffusion rate of lithium ions, thereby reducing lithium plating at the negative electrode during charging.
[0037] Preferably, the ratio of the ternary material to lithium iron phosphate is between (1-3): (7-9). The ratio of the ternary material to the lithium iron phosphate material in different ratios can adjust the voltage required for the battery during charging at different rates. In addition, since the ternary material has a higher lithium ion migration rate and the lithium ions in lithium iron phosphate have a lower migration rate, the lithium ion migration rate of the positive electrode sheet to the negative electrode sheet can be controlled by adjusting the ratio of the two, thereby reducing lithium plating at the negative electrode during charging.
[0038] In some embodiments, the ternary material includes at least one of NCM, NCA, and NCMA.
[0039] Preferably, the ternary material is NCM which has good thermal stability and energy density as well as lower cost.
[0040] Exemplarily, the second positive electrode material layer 3 is composed of 90-100 parts of ternary main material NCM, 0.5-2 parts of PVDF binder, 0.01-0.5 parts of conductive carbon SP, and 0.01-0.5 parts of carbon nanotubes CNT; the first positive electrode material layer 2 is composed of 90-100 parts of lithium iron phosphate main material LFP lithium iron phosphate, 0.5-2PVDF binder, 0.01-0.5 conductive carbon SP, and 0.01-0.5 carbon nanotubes CNT.
[0041] Example 2
[0042] Another aspect of the present invention is to provide a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:
[0043] Step 1: preparing a first positive electrode material layer slurry and a second positive electrode material layer slurry;
[0044] Step 2: selecting the thickness of the upper gasket and the lower gasket according to the solid content of the first positive electrode material layer slurry and the second positive electrode material layer slurry;
[0045] Step 3: Assemble the upper gasket and the lower gasket respectively on the upper and lower cavity positions of the double-layer die head;
[0046] Step 4: putting the first positive electrode material layer slurry and the second positive electrode material layer slurry into a buffer tank and assembling them with a double-layer die head;
[0047] Step 5: The first positive electrode material layer slurry and the second positive electrode material layer slurry are simultaneously coated by double-layer die extrusion coating.
[0048] like Figure 2 , 3 As shown, in order to take into account the dual cores of high energy density and super fast charging of batteries, double-layer coating technology came into being. The positive electrode double-layer coating technology has broad application prospects in the field of lithium-ion batteries, especially in the application scenarios of pursuing high energy density and fast charging. By using double-layer coating technology, the first positive electrode material layer slurry and the second positive electrode material layer slurry with different characteristics can be coated at the same time, which is conducive to the fusion between the interfaces of the two coatings, which not only helps to enhance the adhesion between the layers, but also improves the transmission efficiency of electrons and ions. Especially in the process of charging and discharging at higher rates, good interface fusion helps to stabilize the material structure, prevent material shedding and improve the stability of the battery.
[0049] In some embodiments, the second positive electrode material layer slurry includes NCM, PVDF binder, methyl pyrrolidone NMP, conductive carbon SP, carbon nanotubes CNT, the first positive electrode material layer slurry includes lithium iron phosphate main material LFP lithium iron phosphate, PVDF binder, methyl pyrrolidone NMP, conductive carbon SP, carbon nanotubes CNT,
[0050] Preferably, the solid content of the second positive electrode material layer slurry is 37% to 45%, and the solid content of the first positive electrode material layer slurry is 37% to 49%. The solid content of the second positive electrode material layer slurry and the first positive electrode material layer slurry can be adjusted by adjusting the content of methylpyrrolidone NMP. The solid content within the scope of the present application is conducive to the fusion of the interface between the first positive electrode material layer 2 and the second positive electrode material layer 3, and the solid content within the scope of the present application can form suitable pores after the NMP evaporates after the positive electrode sheet is dried, and form an appropriate porosity after the subsequent rolling of the electrode sheet, in one In some embodiments, the second positive electrode material slurry is composed of 90-100 parts of ternary main material NCM, 0.5-2 parts of PVDF binder, 0.01-0.5 parts of conductive carbon SP, and 0.01-0.5 parts of carbon nanotubes CNT, and then methyl pyrrolidone NMP is added to adjust the solid content of the slurry; the first positive electrode material layer 2 is composed of 90-100 lithium iron phosphate main material LFP, 0.5-2 PVDF binder, 0.01-0.5 conductive carbon SP, and 0.01-0.5 carbon nanotubes CNT are mixed, and then methyl pyrrolidone NMP is added to adjust the solid content of the slurry.
[0051] Preferably, the thickness of the upper gasket is in the range of 0.6 to 0.8 mm, and the thickness of the lower gasket is in the range of 0.8 to 1.0 mm. The present application determines the thickness of the gasket by the solid content of the slurry. When the solid content of the slurry is greater, the viscosity of the slurry is greater, and the thickness of the gasket needs to be set thicker, so that the height of the formed flow channel is also higher, which is conducive to the smooth outflow of the slurry and will not affect the flow state of the slurry. When double-sided coating is performed, the coating flow field of the two slurries is kept stable to reduce the problem of uneven coating thickness or inconsistent coating distribution, which affects the final battery performance.
[0052] Example 3
[0053] (1) Preparation of positive electrode
[0054] The ternary main material NCM, PVDF binder, 1 part conductive carbon SP, and 1 part carbon nanotube CNT are mixed in a mass ratio of 95:1:0.05:0.05, and the solvent NMP is added for stirring to obtain the second positive electrode material layer slurry. The main material of lithium iron phosphate LFP, PVDF binder, 1 part conductive carbon SP, and 1 part carbon nanotube CNT are mixed in a mass ratio of 95:1:0.05:0.05, and the solvent NMP is added for stirring to obtain the first positive electrode material layer slurry; the first positive electrode material layer slurry and the second positive electrode material The layer slurry is evenly coated on the two surfaces of the current collector 1 through a double-layer die head, and after drying at room temperature, it is transferred to a 120°C oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet, wherein the mass ratio of NCM and LFP in the positive electrode sheet is 2:8. In the preparation process of the positive electrode sheet, the porosity of the first positive electrode material layer 2 and the second positive electrode material layer 3 can be controlled by reasonably adjusting the cold pressing process parameters and the addition amount of the solvent NMP. In the present embodiment, the porosity of the first positive electrode material layer 2 is 15%, and the porosity of the second positive electrode material layer 3 is 35%.
[0055] (2) Battery preparation
[0056] The positive electrode sheet, the negative electrode sheet, the separator and the battery casing are assembled and injected with electrolyte. After vacuum packaging, standing, forming, shaping and other processes, a battery is obtained.
[0057] Example 4
[0058] The difference between this embodiment and embodiment 3 is that the porosity of the first positive electrode material layer 2 is 10%, and the porosity of the second positive electrode material layer 3 is 40%.
[0059] The rest is the same as that of Example 3 and will not be described again here.
[0060] Example 5
[0061] The difference between this embodiment and embodiment 3 is that the porosity of the first positive electrode material layer 2 is 20%, and the porosity of the second positive electrode material layer 3 is 30%.
[0062] The rest is the same as that of Example 3 and will not be described again here.
[0063] Example 6
[0064] The difference between this embodiment and embodiment 3 is that the mass ratio of NCM to LFP in the positive electrode sheet is 1:9.
[0065] The rest is the same as that of Example 3 and will not be described again here.
[0066] Example 7
[0067] The difference between this embodiment and embodiment 3 is that the mass ratio of NCM to LFP in the positive electrode sheet is 3:7.
[0068] The rest is the same as that of Example 3 and will not be described again here.
[0069] Example 8
[0070] The difference between this embodiment and embodiment 3 is that the mass ratio of NCM to LFP in the positive electrode sheet is 3:7, the porosity of the first positive electrode material layer 2 is 10%, and the porosity of the second positive electrode material layer 3 is 30%.
[0071] The rest is the same as that of Example 3 and will not be described again here.
[0072] Example 9
[0073] The difference between this embodiment and embodiment 3 is that the mass ratio of NCM to LFP in the positive electrode sheet is 1:9, the porosity of the first positive electrode material layer 2 is 10%, and the porosity of the second positive electrode material layer 3 is 40%.
[0074] The rest is the same as that of Example 3 and will not be described again here.
[0075] Comparative Example 1
[0076] The difference between this embodiment and embodiment 3 is that the porosity of the first positive electrode material layer 2 is 50%, and the porosity of the second positive electrode material layer 3 is 40%.
[0077] The rest is the same as that of Example 3 and will not be described again here.
[0078] Comparative Example 2
[0079] The difference between this embodiment and embodiment 3 is that the mass ratio of NCM to LFP is 1:20.
[0080] The rest is the same as that of Example 3 and will not be described again here.
[0081] Comparative Example 3
[0082] The difference between this embodiment and embodiment 3 is that the mass ratio of NCM to LFP is 20:1.
[0083] The rest is the same as that of Example 3 and will not be described again here.
[0084] Thermal Abuse Test
[0085] After the battery cell is fully charged, place it in a temperature box and heat it under the following conditions: the temperature box is raised from the test environment temperature to 130℃±2℃ at a rate of 5℃ / min, and this temperature is maintained for 30 minutes before stopping heating: After completing the above test steps, observe for 1 hour at the test environment temperature to see if the battery temperature drops. If the temperature drops, set the maximum temperature of the test environment to rise by 2℃, and repeat the above steps until the battery temperature continues to rise. Determine the last environment temperature where the battery temperature continues to rise as the maximum temperature of the battery thermal abuse.
[0086] Charging rate lithium deposition window test
[0087] Install the test battery on the test instrument and place it in a (25±1)℃ test environment. Set the following program: let it stand for 10 minutes: charge to 4.2V at 2.0C constant current, then charge at constant voltage until the current drops to 0.05C, and stop charging; let it stand for 5 minutes; then discharge to 4.5V at 1.0C constant current, repeat the above charge and discharge steps 5 to 10 times, then disassemble the battery to observe the lithium deposition at the negative electrode. If lithium deposition is found at the negative electrode, the charging rate is the battery's charging rate lithium deposition window. If no lithium deposition is found at the negative electrode, set the constant current charging current rate to increase by 0.1C, and repeat the above steps until lithium deposition appears at the negative electrode of the battery.
[0088] The specific experimental data are shown in Table 1.
[0089] Table 1
[0090]
[0091] According to the comparison between Example 3 and Comparative Example 1, it can be seen that when the porosity of the first positive electrode material layer is too large, the charging rate lithium precipitation window will decrease. This is because the increase in porosity increases the circulation speed of lithium ions at the lithium iron phosphate, so that the lithium ions of the first positive electrode material layer and the second positive electrode material layer can quickly migrate to the negative electrode surface, causing lithium ion accumulation and a decrease in the charging rate lithium precipitation window.
[0092] According to the comparison between Example 3 and Comparative Examples 2 and 3, it can be seen that when the proportion of ternary material and lithium iron phosphate in the positive electrode is too high or too low, the charging rate lithium precipitation window will decrease. This is because if the proportion of ternary material is too high, lithium ions will quickly migrate to the negative electrode surface, causing lithium ion accumulation and a decrease in the charging rate lithium precipitation window. If the proportion of lithium iron phosphate is too high, the charging voltage is too high, resulting in lithium precipitation on the negative electrode surface.
[0093] According to the comparison of Examples 3, 7 and 8, when the proportion of the ternary material increases, the diffusion rate of lithium iron phosphate can be controlled by reducing the porosity of the first positive electrode material layer, so as to achieve staggered diffusion of lithium ions from the ternary material, thereby increasing the charging rate lithium precipitation window.
[0094] The above description shows and describes several preferred embodiments of the present invention, but as before, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept of this article through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A positive electrode sheet, characterized in that; The invention comprises a current collector (1), a first positive electrode material layer (2) coated on the surface of the current collector (1), and a second positive electrode material layer (3) coated on the surface of the first positive electrode material layer (2) away from the current collector (1), wherein the first positive electrode material layer (2) comprises lithium iron phosphate, and the second positive electrode material layer (3) comprises a ternary material, wherein the porosity of the first positive electrode material layer (2) is smaller than the porosity of the second positive electrode material layer (3).
2. The positive electrode sheet according to claim 1, characterized in that: The porosity of the first positive electrode material layer (2) is in the range of 10% to 20%.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The porosity of the second positive electrode material layer (3) is in the range of 30% to 40%.
4. The positive electrode sheet according to claim 1, characterized in that: The thickness of the first positive electrode material layer (2) is 70 um to 100 um, and the thickness of the second positive electrode material layer (3) is 10 um to 30 um.
5. The positive electrode sheet according to claim 1, characterized in that: The ratio of the ternary material to the lithium iron phosphate is between (1-3):(7-9).
6. The positive electrode sheet according to claim 1, characterized in that: The ternary material includes at least one of NCM, NCA, and NCMA.
7. A method for preparing a positive electrode sheet as claimed in claims 1 to 6, characterized in that: The following steps are involved: Step 1: preparing a first positive electrode material layer slurry and a second positive electrode material layer slurry; Step 2: selecting the thickness of the upper gasket and the lower gasket according to the solid content of the first positive electrode material layer slurry and the second positive electrode material layer slurry; Step 3: Assembling the upper gasket and the lower gasket at the upper and lower cavity positions of the double-layer die head respectively; Step 4: putting the first positive electrode material layer slurry and the second positive electrode material layer slurry into a buffer tank and assembling them with the double-layer die head; Step 5: simultaneously coating the first positive electrode material layer slurry and the second positive electrode material layer slurry by double-layer die extrusion coating.
8. The method for preparing the positive electrode sheet according to claim 7, characterized in that: The second positive electrode material layer slurry includes NCM, PVDF binder, methyl pyrrolidone NMP, conductive carbon SP, carbon nanotubes CNT, and the first positive electrode material layer slurry includes lithium iron phosphate main material LFP lithium iron phosphate, PVDF binder, methyl pyrrolidone NMP, conductive carbon SP, carbon nanotubes CNT.
9. The method for preparing the positive electrode sheet according to claim 7, characterized in that: The solid content of the second positive electrode material layer slurry is between 37% and 45%, and the solid content of the first positive electrode material layer slurry is between 37% and 49%.
10. The method for preparing the positive electrode sheet according to claim 7, characterized in that: The thickness of the upper gasket is in the range of 0.6 to 0.8 mm, and the thickness of the lower gasket is in the range of 0.8 to 1.0 mm.
Citation Information
Patent Citations
Dual-layer structure positive electrode plate and fabrication method and application thereof
CN109560249A
Positive electrode plate and lithium ion battery
CN110660961A
Multilayer composite positive pole piece, preparation method thereof and lithium ion battery
CN115133008A
Elastic layered ternary positive pole piece and lithium ion battery based on same
CN214477542U
Manufacturing method of electrode for secondary battery
JP2014049240A